Filamin depletion blocks endoplasmic spreading and destabilizes force-bearing adhesions - Lynch, Christopher D. (The American Society for Cell Biology, 2011)
Cell motility is an essential process that depends on a coherent, cross-linked actin cytoskeleton that physically coordinates the actions of numerous structural and signaling molecules. The actin cross-linking protein, filamin (Fln), has been implicated in the support of three-dimensional cortical actin networks capable of both maintaining cellular integrity and withstanding large forces. Although numerous studies have examined cells lacking one of the multiple Fln isoforms, compensatory mechanisms can mask novel phenotypes only observable by further Fln depletion. Indeed, shRNA-mediated knockdown of FlnA in FlnB(–/–) mouse embryonic fibroblasts (MEFs) causes a novel endoplasmic spreading deficiency as detected by endoplasmic reticulum markers. Microtubule (MT) extension rates are also decreased but not by peripheral actin flow, because this is also decreased in the Fln-depleted system. Additionally, Fln-depleted MEFs exhibit decreased adhesion stability that appears in increased ruffling of the cell edge, reduced adhesion size, transient traction forces, and decreased stress fibers. FlnA(–/–) MEFs, but not FlnB(–/–) MEFs, also show a moderate defect in endoplasm spreading, characterized by initial extension followed by abrupt retractions and stress fiber fracture. FlnA localizes to actin linkages surrounding the endoplasm, adhesions, and stress fibers. Thus we suggest that Flns have a major role in the maintenance of actin-based mechanical linkages that enable endoplasmic spreading and MT extension as well as sustained traction forces and mature focal adhesions.